As cooperativas como agentes de transição energética e desenvolvimento regional no Brasil - Villanueva, Bernardo de Almeida (2024)
Português Inglês Cooperativismo Cooperation Cooperativas de energia eletrica Electric cooperatives Comunidades - Desenvolvimento Community development Planejamento regional Regional planning Energia – Fontes alternativas Renewable energy sources Geração distribuída de energia elétrica Distributed generation of electric power Transição energética Energy transition Desenvolvimento energético Energy development   Energy plays a fundamental role in modern society, driving the increase in economic productivity and the population's well-being. In Brazil, hydroelectric power plants have been vital in the electrical sector. Still, there is a growing assessment of alternative energy generation regarding sustainability and social, economic, and environmental impacts. Projections show a decreasing trend in the share of hydroelectric energy, a notable growth in solar energy, and an increase in micro and mini-distributed generation. Accelerating the global energy transition is necessary due to the impacts of climate change, which is a challenge for governments that must balance conflicting agendas. Energy cooperatives have the potential to promote renewable energies and sustainable cities and have been growing in Brazil. This research aims to investigate the potential that Brazilian energy cooperatives may present for energy transition and regional development, identifying their main challenges and proposing strategies for the sector. The study uses a qualitative methodology, collecting data through interviews with representatives of energy cooperatives and related organizations and a systematic review of the literature to support the understanding of the impact of energy cooperatives in Brazil. Interviews reveal that cooperatives are motivated by several factors, including environmental concerns, solidarity economy, and access to solar energy for low-income communities. They play a multifaceted role in the energy transition, promoting energy democratization, cost reduction, and regional development. However, cooperatives face significant challenges such as cultural resistance, lack of understanding, bureaucracy, obtaining financial resources, ambiguous regulation, and the influence of economic power. Law 14.300/2022 is perceived in a mixed manner, with recognition of regulatory stability and concerns about progressive taxation and other aspects. To strengthen the sector, the creation of a federation of energy cooperatives is proposed, inspired by the European REScoop.eu, aiming for greater mobilization capacity. This study offers insights into the role of energy cooperatives in Brazil and their contributions to the energy transition and regional development. The research is innovative in addressing a topic with limited academic production. It fills a gap in the Brazilian context, providing theoretical and practical information that can be applied to improve the renewable energy sector and enhance its environmental, economic, and social benefits